Perancangan Sistem Informasi Stock Opname Berbasis Web Pada Umkm Ilhamum-Taza - Desi Ramadhani; Tanto Tanto; Desti Pusparani (Journal of Applied Accounting and Business, 2022)
UMKM (micro, small and medium enterprises) Ilhamum-Taza is engaged in the production and sale of tempeh chips and peanut brittle which is one of the souvenirs from Jambi. MSME Ilhamum-Taza manages records in the form of stock items that are still manual, so that the recording of goods is not yet effective and efficient. So in order to be more optimal, it must use a web-based inventory information system and use the FIFO (first in first out) method. The development of this web-based stock information system uses the waterfall model and the data flow model using DFD (Data Flow Diagrams) and databases. This research and design produces a stock taking information system that will be implemented in Ilhamum-Taza.